Origin of TAA genes in charophytes: New insights into the controversy over the origin of auxin biosynthesis - Romani, Facundo Alihuen (2017)
There is a current controversy around the origin of auxin biosynthesis genes in plants. Auxin is one of the most important plant hormone and its major biosynthesis pathway implies the tryptophan aminotransferase (TAA) and flavin containing monooxygenases (YUCCA) gene families (Mashiguchi et al., 2011). The hormone is present in all land plants and also in charophycean algae. Recently, it was demonstrated that algae also respond to auxin (Stirk et al., 2013; Ohtaka et al., 2017), but the presence of the biosynthesis genes in this lineage is still not clear.